0456 Comparative Safety and Efficacy of Hypnotics: A Quantitative Risk-Benefit Analysis. (25th May 2022) - Cheung, Janet; Scott, Hannah; Muench, Alexandria; Morales, Knashawn; Grunstein, Ronald; Krystal, Andrew; Riemann, Dieter; Perlis, Michael
Abstract: Introduction: Hypnotics continue to be preferentially used in practice for the treatment of chronic insomnia, yet the comparative safety and efficacy of medication options are unclear. While several position statements and network meta-analyses have provided some guidance, none have provided a quantitative assessment of risk-benefit. In the present analysis, each therapeutic class commonly used for chronic insomnia is quantitatively ranked with respect to safety, efficacy, and risk-benefit. Methods: Safety data for FDA-approved hypnotics were extracted from the package insert adverse event tables and standardized to form a placebo-adjusted adverse event rate per 1000 (AEr). Efficacy data were extracted from randomized controlled trials identified in professional society position statements and published systematic reviews. The efficacy metric was computed from placebo adjusted pre-post change scores for self-reported sleep continuity (i.e., sleep latency [SL], wake after sleep onset [WASO], and total sleep time [TST]) and represented as a summed composite effect size score (SWT). Risk-benefit (R/B) was represented as a ratio between AEr and SWT. Comparative safety, efficacy, and risk-benefit metrics were calculated for five therapeutic classes: Benzodiazepines (BZs), non-benzodiazepine benzodiazepine receptor agonists (BZRAs), dual orexin receptor antagonists (DORAs), melatonin receptor agonists (MELAs), and sedating antidepressants (SADs). Results: With respect to safety, MELAs had the lowest adverse event rate (AEr=43.1) and BZRAs had the highest rate (AEr=255.0). With respect to efficacy, BZs were the most efficacious (SWT=1.94, Mean ES=0.59) and MELAs were least efficacious (SWT=0.11, Mean ES=0.02). Overall, with respect to risk-benefit, SADs had the most favorable profile (R/B=69.5), while MELAs had the least favorable profile (R/B=395.7). Conclusion: The optimal selection of hypnotics requires consideration of both risk and benefit. Findings suggest that SADs can be considered the first-line pharmacotherapeutic option due to the superior risk-benefit profile. If treatment responses are inadequate or if SADs are contraindicated, risk-benefit rankings may serve as a decision tree as part of a medical algorithm protocol to guide treatment selection for patients with chronic insomnia. Support (If Any): Sleep Research Society Mentor-Mentee Award (Cheung); K24AG055602 & R01AG054521 (Perlis)